2015
DOI: 10.1093/jee/tov051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heat Shock Protein Genes in Different Developmental Stages and After Temperature Stress in the Maize Weevil (Coleoptera: Curculionidae)

Abstract: DisclaimerThe United Nations Environment Programme (UNEP), the Technology and Economic Assessment Panel (TEAP) Co-chairs and members, the TEAP Task Forces Co-chairs and members, and the companies and organisations that employ them do not endorse the performance, worker safety, or environmental acceptability of any of the technical options discussed. Every industrial operation requires consideration of worker safety and proper disposal of contaminants and waste products. Moreover, as work continues -including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Heat shock increases three heat shock protein (hsp) genes hsps—Szhsp70 , Szhsc70 , and Szhsp90 expression in S . zeamais with the highest upregulation at 40°C, and the intensity of upregulation is ranked as follows: Szhsp70 > Szhsp90 > Szhsc70 [ 43 ]. The present results indicated that hsp70 and trpA1 genes of T .…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock increases three heat shock protein (hsp) genes hsps—Szhsp70 , Szhsc70 , and Szhsp90 expression in S . zeamais with the highest upregulation at 40°C, and the intensity of upregulation is ranked as follows: Szhsp70 > Szhsp90 > Szhsc70 [ 43 ]. The present results indicated that hsp70 and trpA1 genes of T .…”
Section: Discussionmentioning
confidence: 99%
“…In Sitophilus zeamais (Tungjitwitayakul et al . ), SzHsp70 exhibited higher transcription levels in sub‐esophageal ganglions and in Malpighian tubules. In addition, SzHsp90 was highly expressed in testes and sub‐esophageal ganglions.…”
Section: Discussionmentioning
confidence: 83%
“…The Hsp19.8 expression levels of S. litura and Hsp19.7, Hsp20, and Hsp20.7 expression levels of Cydia pomonella reached their maxima during the adult stage (Garczynski, Unruh, Guédot, & Neven, ; Shen et al, ). Hsp90 expressed differently in different developmental stages of Plutella xylostella (Sonoda, Ashfaq, & Tsumuki, ) and Sitophilus zeamais (Tungjitwitayakul, Tatun, Vajarasathira, & Sakurai, ). The results of studies on Hsp genes of Hermetia illucens show that the decrease in both Hsp expression levels in the fifth instar larval stage could be imputable to the change in the feeding habits of H. illucens (Giannetto et al, ).…”
Section: Discussionmentioning
confidence: 99%